Eating Habits and Body-weights of Students of the University of Belgrade, Serbia: A Cross-sectional Study (Journal of Health, Population and Nutrition, 2013)
The purpose of this survey was to quantify the prevalence of overweight and obesity among a sample of students in Belgrade University, Serbia and to describe their main eating habits. A total of 1,624 questionnaire responses were analyzed (response rate 97.3%). The students were recruited during mandatory annual check-ups in April-June 2009. All subjects completed the questionnaire; height (in cm) and weight (in km) were measured by two physicians. Results were assessed statistically. Almost every fourth male student was overweight. Strikingly, 15% of female students were underweight. Highly-significant difference was found between average body mass index (BMI) of male and female students (F=317.8, p=0.001). Students BMI did not correlate with average family income or with the frequency of taking breakfast (p=-0.064, p=0.152 for males and ?=0.034, p=0.282 for females respectively). There is a growing demand for global health strategies which would encourage healthy body-image and figure; thus, these initiatives should mobilize the society on a national and international level. DOI: http://dx.doi.org/10.3329/jhpn.v31i3.16824 J HEALTH POPUL NUTR 2013 Sep; 31(3): 330-333